The Humour of Sociolects and Idiolects among Heterogeneous Audiences in Contemporary Nigerian Stand-up Comedies - Idowu James Adekunle (Randwick International of Social Science Journal, 2023)
Stand-up comedy, a trans-tribal and gender-equality profession among talented Nigerian youths, is posed with different linguistic barriers in communication exchange between tribal performers and their heterogeneous audience and between intertribal performers and homogeneous audiences because of cultural differences. In Southwest Nigeria, the Yoruba call it "Efe" and "Apara;" Southeast, the Igbo, "Njakiri;" the North, Hausa/Fulani, "Yan Kama" and 'Waman Sariki. Earlier studies have focused on its entertainment aspects, disregarding its underlying intercultural values and mono-national speech act. Therefore, this study examines the use of the mono-national speech act of Pidgin-sociolect and Pidgin-idiolect (catchphrases and withering scorn) used by Nigerian stand-up comedians in live performances to address linguistic barriers and foster communication exchange between performers and heterogeneous audiences. This is in a bid to create national unity, promote love and foster mutual intelligibility among the heterogeneous audience. Schechner's Performance Theory was used to interrogate performance. Data from live recordings of purposively selected Nigerian Stand-up comedians: Ayo Makun (AY), Helen Paul, Godwin Komone (Gordons), Ahamefula Igwemba (Klint da Drunk), and Aboki, were used. They underwent a performance analysis.